Learning about Risk: Some Lessons from Insurance - Geman, Hélyette (Review of Finance, 1999)
Abstract This paper argues that in the fundamental subject of financial risk analysis, some valuable lessons may be drawn from insurance. The probability of ruin, defined as a first passage time, carries a dynamic element whose absence in Value at Risk is one liability, among others. Extreme value theory, which has been successfully applied to insurance shortly after it was introduced in probability, may offer a coherent framework for analyzing the extreme moves such as the ones observed in recent foreign exchange and financial crises. Lastly, we show that the genuine hazards generated by global capital markets and illustrated by the events of summer 1998, generate a market incompleteness that existing models of defaultable bonds do not fully address. In contrast, the long experience of risk premium analysis in the insurance and reinsurance industry, as well as the existence of historical data on natural disasters, render the valuation of catastrophe bonds less perilous than that of defaultable bonds.